Growth of bilayer MoS2 flakes by reverse flow chemical vapor deposition - Nguyen, Van Tu; Nguyen, Van Chuc; Tran, Van Hau; Park, Ji Yong (Materials Letters, 2023)
In this work, we report on the low temperature growth of bilayer MoS2 by reverse flow chemical vapor deposition (CVD) with MoO3 and S powder as precursors, respectively, while reverse flow is facilitated by adding a one-end sealed small quartz tube inside the CVD setup. Most of the as-grown flakes are bilayer MoS2 with a high yield of 85 % in the statistical analysis. Field effect transistors (FET) based on as-grown bilayer MoS2 flakes behave as n-type semiconductors with a switching ratio of ∼105 as well as carrier mobility of ∼3.2 cm2 V−1 s−1. This work demonstrates a promising simple approach to grow bilayer flakes of other two-dimensional materials such as MoSe2, WS2, and their heterostructures.
Keywords: As-grown; Bi-layer; Bilayer flake; Chemical vapor deposition growth; Chemical vapour deposition; Field effect transistor device; Field-effect transistor; Low temperature growth; Quartz tubes; Reverse flow; Bilayer flakes; CVD growth; FET device; MoS2